“Who Are They?”: An Exploratory Study Om Malaysian Outbound Travellers - Chong, Voon Choong (2010)
Since the turn of the century Malaysia has emerged as one of the biggest beneficiary of international tourism expansion. Its tourist arrivals triple in the last ten years from 1999 to 2009. In addition as the key recipient of international tourists, Malaysia emerges as one of the major forces to be reckoned with in terms of outbound tourism. The importance of Asia and the Pacific outbound travellers, including Malaysian, would be further enhanced with a projected growth higher than the world average. Despite its growing significance and recognition by World Tourism Organization as the most promising growth area, limited studies were carried out on Asia outbound tourism, let alone Malaysia. It is therefore to the interest of this paper to initiate an exploratory study on the Malaysian outbound travellers. This paper aims to understand who are these Malaysian outbound travellers, what is their socio-demographic profiles, what is the characteristics of the journey they make, how their travel arrangement looks like, how do they pick leisure destination and how information technology impact their travel planning. The study attempts to shed light on useful insight for those interested in outbound travellers from Malaysia. Destination suppliers and tourism marketers can leverage on these insights to strategize their marketing mix to meet the demand of Malaysian outbound travellers with a better tailored travel product and services.